Mobile Device Applications for the Visualization of Functional Connectivity Networks and EEG Electrodes: iBraiN and iBraiNEEG - Rojas, Gonzalo M.; Fuentes, Jorge A.; Gálvez, Marcelo (Frontiers in Neuroinformatics, 2016)
Multiple fMRI-based functional connectivity networks were obtained by Yeo et al., and the visualization of these complex networks is a difficult task. Also, the combination of functional connectivity networks determined by fMRI with EEG data could be a very useful tool. Mobile devices are becoming increasingly common among users, and for this reason, we describe here two applications for Android and iOS mobile devices: one that shows in an interactive way the seven Yeo functional connectivity networks, and another application that shows the relative position of 10-20 EEG electrodes with Yeo’s seven functional connectivity networks.